Revitalizing state and local public service : strengthening performance, accountability, and citizen confidence - 4 0 16; Thompson, Frank J.; 5 National Commission on the State and Local Public Service (San Francisco : Jossey-Bass Publishers, 1993)
Jossey-Bass public administration series. Collection of expert researchers' contributions to the ongoing debate over reforming public service.
A publication of the National Commission on the State and Local Public Service.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; State governments;Local government -- United States.;United States. -- 20; 20; 2